MP51: Assessment of predictors of deterioration in mild traumatic brain injury with intracranial hemorrhage at emergency department. (May 2019) - Fortier, É.; Paquet, V.; Émond, M.; Chauny, J.; Hegg, S.; Malo, C.; Champagne, J.; Gariepy, C.; Carmichael, P.
Abstract : Introduction : Mild traumatic brain injury (mTBI) with intracranial hemorrhage (ICH) is a common cause of Emergency Department (ED) visits. Over the past years, several authors have debated the relevance of radiological and clinical follow-up of these patients, as the main challenge is to identify patients at risk of clinical deterioration.Objectives : To determine whether demographic, clinical or radiological variables can predict patient deterioration.Methods : Design: An historical cohort was constituted in two level-1 trauma centers (Chu de Quebec - Hôpital de l'Enfant-Jésus (Québec City) and Hôpital du Sacré-Coeur (Montréal)).Participants : Medical records of mTBI patients aged ⩾16 with an ICH were reviewed using a standardized data collection tool. Consecutive medical records were reviewed from the end of 2017 backwards until sample saturation.Measures : Deterioration was defined as either death, deterioration of the control CT scan according to the radiologist, clinical deterioration or neurosurgical intervention.Analyses : Logistic regression analyses were performed to ascertain predictors of deterioration. Interobserver agreement was calculated.Results : A total of 274 patients were included in our analyses. Mean age was 60.8 and 68.9% (n = 188) were men. Four variables were found to be associated with all outcomes: radiological deterioration, clinical deterioration, death, and neurosurgical intervention. Diabetes (odds ratio (OR) = 2.6, 95% CI [0.97-6.94]), confusion as an initial symptom (OR = 2.8, 95% CI [1.42-5.61]), anticoagulation (OR = 2.8, 95% CI [1.01-7.84]) and significant subdural hemorrhage (≥4 mm) (OR = 3.4, 95% CI [1.42-5.61]) seen on the first computed tomography scan were strongly associated with these outcomes. Age had a neutral effect (OR = 1.01, 95% CI [0.99-1.03]) while high initial Glasgow Coma score seemed to have a protective effect (OR = 0.4, 95% CI [0.24-0.69]). Radiological deterioration was not systematically associated with clinical deterioration. As for the 46 patients with a deterioration of CT scan, only 30.4% vs. 69.5% without deterioration (p = 0.0035) showed a clinical deterioration.Conclusion : Diabetes, anticoagulation, significant subdural hemorrhage and confusion as an initial symptom seem to be predictors of deterioration following a mild traumatic brain injury with positive CT scan.